A aposentadoria especial no regime geral de previdência social no Brasil: o meio ambiente de trabalho e a teoria da consequência à causa - Oliveira, Alexandre Bittencourt Amui de (2020)
This paper to discuss how special retirement is presented in the national legal system, in particular to identify if it is a kind of generic compensation due to the workplace in an unhealthy work environment, based on analysis of the theory of cause. We’ll search understand whether the special retirement, granted to those who work in environments that are harmful to their health or physical integrity, is a legitimator of the aggression against the dignity of the worker, in clear offense to the fundamental right, which is life, or if it is an effective instrument to fight the causes responsible for illnesses or accidents caused by the workplace. The objectives of the work are to study the conceptual evolution of the requirements for the granting of special retirement in the General Social Security System in Brazil, to identify the concept of a healthy-work environment and its effects for social security purposes through the theory of cause to and to check if how special retirement presents itself as an instrument to guarantee the health of the work environment. The aim is to conclude, through the deductive method, to demonstrate that the constitutional norm, in its essence, guarantees a healthy working environment, avoiding generic exceptions, so that life, integrity and dignity will always prevail over merely economic interests.